Technical writing in the modern world - Minas, Rebecca M.; Ferianiza, Marilyn B. (Intramuros, Manila, Philippines : Mindshapers Co. Inc., 2008)
"This book is intended to facilitate the college students in learning how to write correctly and effectively on different subject areas." --- Introduction.
Chapter I. Nature of technical writing -- Chapter II. Basics -- Chapter III. Applications.
Includes bibliographical references.
Keywords: TECHNICAL WRITING